THE LEGITIMIZING POWER OF HADITH IN ANTI-MAULID DISCOURSE: A CRITICAL DISCOURSE ANALYSIS OF SALAFI IDEOLOGY ON SOCIAL MEDIA - Rohmah, Nur Maulidya Wardatur; Zamzami, Mukhammad; Hegazy, Wael; Lutfi, Muhammad (Nabawi: Journal of Hadith Studies, 2025)
This article critically examines the use of hadith in constructing the anti-Maulid narrative concerning the celebration of the Prophet’s Birthday disseminated through the Instagram account @foto.video.islam, using Teun A. van Dijk’s Critical Discourse Analysis (CDA) as an analytical lens. The study focuses on how Salafi ideology is articulated and propagated through religious discourse in the digital sphere. The research problem addresses how hadiths are selectively cited to delegitimize the celebration of the Prophet’s Birthday while undermining the authority of scholars who support it. This qualitative descriptive study analyzes the macrostructure, superstructure, and microstructure of the discourse produced by the account. The findings demonstrate that the use of hadith functions as a tool of ideological legitimation, consolidating Salafi authority within the digital space and marginalizing alternative perspectives in the broader landscape of Islamic intellectual traditions. This strategy is not merely textual or jurisprudential but reflects complex ideological operations that shape perceptions and religious orientations in contemporary digital public spheres. The study also highlights the importance of critical awareness regarding the politicization of religious texts and underscores the need for ethical dialogue and mutual respect across theological differences, ensuring that sectarian divergences do not become sources of social conflict or hierarchical domination. Overall, the research shows that digital anti-Maulid discourse mobilizes hadith as a means to construct and maintain religious authority, while emphasizing the broader implications for critical engagement and responsible communication in diverse Islamic communities.[Artikel ini secara kritis menelaah penggunaan hadis dalam konstruksi narasi anti-Maulid mengenai perayaan Maulid Nabi yang disebarkan melalui akun Instagram @foto.video.islam, dengan menggunakan lensa Teun A. van Dijk’s Critical Discourse Analysis (CDA). Penelitian ini memfokuskan pada bagaimana ideologi Salafi diartikulasikan dan dipropagandakan melalui wacana keagamaan di ruang digital. Masalah yang diteliti adalah bagaimana hadis dipilih dan disajikan secara selektif untuk mendiskreditkan perayaan Maulid serta meremehkan otoritas ulama yang mendukungnya. Penelitian ini bersifat kualitatif deskriptif dan menganalisis struktur makro, superstruktur, dan mikro dari wacana yang dihasilkan akun tersebut. Hasil penelitian menunjukkan bahwa penggunaan hadis oleh akun ini berfungsi sebagai alat legitimasi ideologis, memperkuat posisi Salafi dalam ranah digital, dan memarginalkan perspektif lain dalam tradisi intelektual Islam. Strategi ini tidak hanya bersifat tekstual atau yuridis, tetapi juga mencerminkan operasi ideologis kompleks yang membentuk persepsi dan orientasi keagamaan dalam masyarakat digital kontemporer. Penelitian ini juga menekankan pentingnya kesadaran kritis terhadap politisasi teks agama dan perlunya menjaga etika dialog serta saling menghormati antarmazhab, sehingga perbedaan teologis tidak menjadi sumber dominasi atau konflik sosial. Secara keseluruhan, penelitian ini menunjukkan bahwa wacana anti-Maulid digital memobilisasi hadis sebagai sarana konstruksi dan pemeliharaan otoritas keagamaan, sekaligus menyoroti implikasi yang lebih luas terkait keterlibatan kritis dan komunikasi yang bertanggung jawab dalam komunitas Islam yang beragam.]